Women Empowerment Through Food Production Project in a Peri-Urban Landscape - Adji, Riyanto (UI Scholars Hub, 2025)
The paper discusses a community project related to local food production by a group of women in an idle peri-urban landscape. Instead of positioning women solely as homemakers within the house, this project views them as active participants of a peri- urban community. On the other hand, the availability of idle land in the peri-urban context can be utilized, allowing it to be transformed into an active space for growing food. Responding to the idea, a community project was conducted with a group of women farmers in a housing complex situated near the Bubulak Village, Bogor, Indonesia. They utilized an open space that had been idle for a long time and transformed it into a community farming space, a productive land for cultivating vegetables and other horticultural plants. To support the enthusiasm for this project, a training program was conducted to produce liquid organic fertilizer and compost, aiming to increase plant productivity through an organic method. The process was observed qualitatively, with a particular focus on the transfer of knowledge. As this community values a healthy lifestyle, the introduction of organic fertilizer becomes a crucial foundation for creating potential business ventures that can drive the family and local economy. Furthermore, as this project highlights the critical role of women in everyday life, it involves two key activities in transforming idle landscapes—producing organic fertilizer and formulating a potential business venture. The empowerment project in this study has demonstrated a positive impact on the community’s resilience in producing and maintaining high-quality local food.